ANALISA SENTIMEN TERHADAP TAGAR #dirumahaja MELALUI TWITTER DI INDONESIA - ANDREYESTHA; ADHI DHARMA SURIYANTO; WITRIANA ENDAH PANGESTI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
New Normal now inevitably apply in various fields. During the Covid-19 pandemic, people were required to do various things in their own homes. Social media is increasingly being used by the community, one of which is that Twitter has many functions and purposes. Twitter can disseminate information in the form of appeals, such as dirumahaja hashtags echoed by the government and the people of Indonesia. The use of these dirumahaja hashtags has various kinds of opinions, such as positive and negative opinions. This study tries to analyze Indonesian language tweets that use dirumahaja hashtags to find out how people in Indonesia view these hashtags. The method used is scraping data from Twitter with a total of 200 data tweets then analyzed using the lexicon-based text mining method, the sentiment results obtained from tweets using the Bing Vector method. The results of the sentiment analysis in this study got a positive score of 49, and a negative score of 48. The negative score almost offset the positive score due to the high percentage of Anticipation emotions of 40% which illustrates the concern of Twitter netizens about the COVID-19 pandemic which they pour through dirumahaja tagged tweets.